Review of the grunt genus Rhonciscus (Lutjaniformes: Haemulidae) from the Western Atlantic, with the description of a new species from Brazil - Marceniuk, Alexandre Pires; Caires, Rodrigo Antunes; Rotundo, Matheus Marcos; Gasparini, João Luiz; Brito, Gitá Juan Soterorudá; Castilho, Júlia Cristina [UNESP]; Cerqueira, Najila Nolie Catarine Dantas [UNESP]; Oliveira, Claudio [UNESP]; Espindola, Vinicius Corrêa (Springer Nature, 2024)
The genus Rhonciscus Jordan & Evermann, 1896 (Haemulidae) was recently revalidated, and it brought together four species allocated along with Pomadasys Lacepède, 1802, two from the Western Atlantic and two from the Eastern Pacific. However, the status of some of the species in the western South Atlantic was still doubtful. This study aims to review Rhonciscus species from the Western Atlantic based on morphological and genetic data. Our results bring the re-creation and redefinition of the limits of Rhonciscus crocro (Cuvier, 1830) and R. approximans Bean & Dresel, 1884 with the recently described R. pauco Tavera, Schärer-Umpierre & Acero P., 2022 as a junior synonym, with a description of a new species of Rhonciscus. The new species, distinguished by a very long snout and short upper jaw, is from the Brazilian coast. A further evaluation of the status of Pristipoma cultriferum Poey, 1860 and Pristipoma ramosum Poey, 1860, described from Cuba, is also provided.
Keywords: Biogeography; Cytochrome c oxidase subunit I; Evolution; Pomadasys; Taxonomy